The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/4324138
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial Intelligence in Repairing Meniscus Injury in Football Sports with Perovskite Nanobiomaterials

Abstract: Knee meniscus injuries are more likely to occur in young adults in clinical practice, and their lower age of onset and greater impact on joint function after injury also put forward higher requirements for the treatment and rehabilitation of meniscus injuries. With the rapid development of artificial intelligence technology and arthroscopic minimally invasive technology, arthroscopic meniscus plasty and perovskite nanobiomaterial repair have gradually replaced the previous open meniscus surgery of the knee joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Before and after the evaluation, when the patient's muscles were completely relaxed and when there was no dynamic support of the Lokomat system, L-ROM was used to evaluate the range of motion of the affected knee joint by measuring the arc of motion through which the joint was moved by external force [22]. (2) In the observation of knee function, Lysholm scores and the International Knee Documentation Committee (IKDC) scores of knees were used to measure knee reoperation before and 6 months after labor. (3) To determine quality of life, the World Health Organization Quality of Life Scale-Short Form Questionnaire (WHO-QOL-BREF) was used to determine quality of life in two groups before and after surgery: WHOQOL-BREF included social work and life support and included physical and mental activity [23].…”
Section: Observation Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before and after the evaluation, when the patient's muscles were completely relaxed and when there was no dynamic support of the Lokomat system, L-ROM was used to evaluate the range of motion of the affected knee joint by measuring the arc of motion through which the joint was moved by external force [22]. (2) In the observation of knee function, Lysholm scores and the International Knee Documentation Committee (IKDC) scores of knees were used to measure knee reoperation before and 6 months after labor. (3) To determine quality of life, the World Health Organization Quality of Life Scale-Short Form Questionnaire (WHO-QOL-BREF) was used to determine quality of life in two groups before and after surgery: WHOQOL-BREF included social work and life support and included physical and mental activity [23].…”
Section: Observation Indicatorsmentioning
confidence: 99%
“…With social progress, economic development, the improvement of residents' living standards, and the rise of national sports, people are paying more and more attention to their physical fitness and health, which makes more people join sports. In the process of exercising, due to the lack of understanding of the exercise load, exercise time, and correct exercise posture that oneself can bear, it is bound to cause sports injuries in some parts of the body [ 1 , 2 ]. The meniscus is the cartilage between the tibia and the femur, one on each side.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has identified artificial intelligence (AI) as a tool to predict the need for overnight hospital stays in ligament surgery and total knee arthroplasty (TKA) [ 8 ]. AI has also contributed to new advanced treatments of meniscus injuries [ 9 ]. Orthopedic surgery has made significant progress by adapting new techniques as arthroscopy in the last century and machine learning possess another potential for a ground breaking shift towards optimal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…4IR has attracted considerable academic attention as a new trend towards automation and as a positive response to the lack of growth of new industries [17]. The field of sports medicine under the influence of 4IR has also seen a part of emerging research in the 21st century, such as sports medicine and artificial intelligence [8], biomimetic materials in sports medicine [18,19], the use of big data in sports medicine [20,21]. The impact of 4IR on the field of sports medicine is also much more than what has been mentioned, according to a search on PubMed it was found that keywords related to 4IR…”
Section: Technologies Directly Related To 4irmentioning
confidence: 99%